Os efeitos do yoga sobre parâmetros cognitivos e afetivos no envelhecimento saudável - Rodrigues, Mônica dos Santos (2019)
Context: Brazil is facing a fast aging process. Cognitive decay and complaints are frequent in elder population, mostly about memory and attention. Objectives: Verify the effects of Hatha Yoga on attention, memory and relationed parameters, like anxiety and depression, in healty elders. Method: 28 brazilian elderly participated, aged between 59 and 73, they were separated in: 14 volunteers for a 15 days intervention (Yoga=6; Stretching=8); and 14 volunteers for a 3 months intervention (Yoga=8; sedentary control=6). The cognitive and affective evaluation was realized before and after those interventions and included: (i) D2Test, Concentrated Attention; (ii) Mindfullness Facets Quiz (FFMQ-BR); (iii) Prospective and retrospective memory quiz (QMPR); (iv) Subtest of Numbers and Letters Sequency (WAIS III; and (v) the Anxiety and Depression Hospital Scale (HAD). Results: Comparing those groups after the short intervention, significant differences in the variables Liquid Result (RL) (U= 5,5; z= -2,39; p<0,01) of D2 test; facet 3 (Watching) of Mindfulness (U= 5,50 z=- 2,41; p<0,01) and depression symptoms (U= 8,5; z=-2,05; p<0,04) were identified. Yoga group showed better attention performance and reduced symptoms levels. When comparing the pre and post phases of the Yoga group, were found optimization tendencies in RLvariables, Raw Score (RB), facet 1 (not judging internal experience) and 4 (Describing – positive formulation) of Mindfullness. After etended intervention wasn’t found significant differences between the groups, however, the Yoga group shows significant improvement in post phase about facet 6 (non-reactivity to intern experience) of Mindfullness and Prospective and Retrospective Memory (z=-2,52; p<0,008) and tendencies about operacional memory (z= -1,86; p<0,07) and anxiety symptoms (z= -1,98; p<0,07). Wasn’t found any significant improvement in control groups of both interventions. Conclusion: The results suggests that the regular practice of Hatha Yoga, even for a short period of time, have the potential to benefit the studied memory and attention aspects, as well as reduce the noticed levels of anxiety and depression in healthy elderly in the context o four country.